35.1k views
2 votes
A system of equations is shown below: n = 3m + 6 n − 2m = 2 What is the solution, in the form (m, n), to the system of equations? (−4, −6) (−5, −9) (2, 6) (1, 8)

User Ruseel
by
7.6k points

2 Answers

3 votes

n=3m+6 \\ n-2m=2 \\ \\ \hbox{substitute 3m+6 for n in the second equation:} \\ 3m+6-2m=2 \\ m+6=2 \\ m=2-6 \\ m=-4 \\ \\ n=3m+6=3 * (-4)+6=-12+6=-6 \\ \\ \boxed{(m,n)=(-4,-6)}
User Loki Kriasus
by
7.1k points
1 vote

Answer:


(-4,-6).

Explanation:

We have been given a system of equations and we are asked to find the solution for given system of equations in the form (m,n).


n=3m+6...(1)


n-2m=2...(2)

We will use substitution method to solve linear equation. Upon substituting equation (10 in equation (2) we will get,


3m+6-2m=2

Combine like terms:


m+6=2


m+6-6=2-6


m=-4

Substituting
m=-4 in equation (2) we will get,


n-2* -4=2


n+8=2


n+8-8=2-8


n=-6

Therefore, the solution for our given system of equation is
(-4,-6).

User Miles Alden
by
7.6k points